Dr. F.A. Wickramasinghe Oration 2015 Beyond borders: enhancing public health security at points of entry to Sri Lanka - Vindya Kumarapeli (Journal of the College of Community Physicians, 2017)
We live in a unique and unprecedented era in human history. We are more divided as humanity yet more connected, laced and knitted than ever before. Infectious disease pandemics, radio-nuclear or toxic industrial accidents, conflicts, and natural disasters have emerged as threats to global public health security during the past few decades.